Rural development policies in European Union and Latin America: a few reflexions for Costa Rica´s case. 1990-2008 - Blanco Obando, Edgar Eduardo (2019)
Through a large analysis of literature about development policies, statistics and studies of cases in European Union and Latin America, this article presents an analysis of main development rural policies in European Union, Latin America and Costa Rica between 1990 and 2008, when globalization produced a new reality in rural sectors that forced to create modern actions for rural development. Thus, it´s been evidenced that in these regions, territorial bottom-up rural policies caused social inequality and did not resolve the main issue: the rural poverty.